AVALIAÇÃO DA QUALIDADE DA SUBSOLAGEM EM DIFERENTES CONDIÇÕES DE SOLO - Gonçalves, Saulo Boldrini (2014)
The subsoil is a tillage operation was consolidated in forest area due to its beneficial to plants and operational advantages effects. But there are several questions about what ideal to be used in each condition of the soil and the depth to be imaged equipment?This study aimed to perform an operational and quality assessment of mechanical preparation in different soils and depths for forest deployment. Data were collected in the company`s operating areas of Klabin SA, located in the municipality of Telemaco Borba, PR. The was studied a mechanical preparation system with a Crawler tractor equipped with subsoiler. Sample plots were located in forest areas covering two soil: Latossolo Vermelho a very clayey soil (soil A) and Latossolo Vermelho Amarelo typic sandy texture (soil B). The treatments were the working depths subsoiler 40 and 50 cm in soil (SA-40 and SB-50) and the same depth to the soil B (SB-40 and SB-50). Initially it was determined the mechanical availability, operational efficiency and productivity of the equipment in the implementation of mechanized preparation of the soil. Quality data were analyzed with the use of quality control tools such as histograms and control charts . The results showed that there wasn`t significant changes (p < 0.05) in mechanical availability, operational efficiency and productivity in the depths of assessed work in the same soil A or B. Both soils had PR values above the critical value (2 MPa) in the layer 0-40 cm depth, in the pre subsoiling moment. The distance class that showed higher soil resistance to penetration was 0 50 cm. This fact is explained to increased traffic of harvesting machines on the edge of the stand. The depth and groove format were under the control of the process of soil preparation for the treatments SA- 40 and SA-50 , and lack of control for the treatments SB-40 and SB-50. The percentage of depth measurements in the center of the groove, which reached the company`s specified limit (50 cm for clayey soils), was 22.6 and 40.6 % for the SA-40 and SA-50 treatments, respectively. In soil B, this percentage was 55. 0 and 84.6 % for SB-40 and SB-50, with the limit set by the company was 40 cm for sandy soils respectively.